(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The article highlights the importance of improving the efficiency of innovation management in the context of globalization. Scientific approaches to innovation concepts are presented. Also, directions of measures implemented in innovative activity in the republic are indicated. In addition to the indicators of the development of the innovative sector in the Namangan region were analyzed, and the existing problems were revealed. Recommendations are also given for the elimination of existing problems and effective development of the sector.